The First Step of Mandatory Environmental, Social and Governance (ESG) Reporting in Thailand and its Effect on Market Reaction - Suttipun, Muttanachai (Journal of Environmental Accounting and Management, 2026)
To reach corporate sustainable development and responsibility of environmental, social and governance (ESG), corporations are growingly aware of the necessity of corporate reporting on their ESG impact. The ESG reporting in Thailand has been changed from voluntary to mandatory reporting. Therefore, this study aims to investigate mandatory ESG reporting of listed companies in Thailand during 2020 to 2022, and to test the influence of ESG reporting on market reaction. Using corporate annual reporting during 2020 to 2022, Top100 listed firms from the Stock Exchange of Thailand (SET) are used as population and samples of this study. The ESG reporting is measured by (1) gas (carbon) emission for environmental reporting, (2) provident fund for social reporting, and (3) human lawsuit for governance reporting, while average stock price is a proxy of market reaction. Descriptive analysis, correlation matrix, and panel regression are used to analyze the data following by objectives of this study. As the results, the pattern of gas emission is an increase during period being study, while the provident fund is a decrease. However, the pattern of human lawsuits is not different. Finally, the study finds the significant influences of provident fund and human lawsuits on market reaction of top100 Thai listed firms. The results of this study are demonstrated that legitimacy, agency, and signaling theories can be used to explain the mandatory ESG reporting in Thailand as well as its impact on market reaction.